Interphase Engineering for Stabilizing Ni‐Rich Cathode in Lithium‐Ion Batteries by a Nucleophilic Reaction‐Based Additive. Issue 7 (8th February 2023) - Zheng, Wei‐Chen; Huang, Zheng; Shi, Chen‐Guang; Deng, Yaping; Wen, Zi‐Hao; Li, Zhen; Chen, Hui; Chen, Zhongwei; Huang, Ling; Sun, Shi‐Gang
Abstract: Ni‐rich cathode materials are considered promising candidates for next‐generation lithium‐ion batteries because of their high energy density and low cost. However, interphase failure at the surface of Ni‐rich cathodes negatively impacts cycling performance, making it challenging to meet the requirements of long‐term applications. In this study, a strategy is developed to improve interphase properties through introduction of a nucleophilic reaction‐based additive, using an appropriate amount of the inducer lithium isopropoxide (LIP) in the commercial electrolyte to achieve long‐term cycling stability of Li||LiNi0.83 Co0.11 Mn0.06 O2 (NCM83) cells. This strategy enables Li||NCM83 cells to maintain a capacity of 148.7 mAh g −1 with a retention of 83.3 % even after 500 cycles. This outstanding cycling stability is attributed to a robust cathode‐electrolyte interphase (CEI) constructed on NCM83 surface LIP‐induce ring‐opening polymerization of ethylene carbonate (EC). As a result, the organic‐inorganic components of the CEI effectively constrain gas evolution and the corresponding phase transformation behavior. Furthermore, the CEI also suppresses microcrack formation and eventually sustains the Ni valence and coordination environment at high voltage. Abstract : Ready, willing, and stable : Interphase stability issues affect the commercialization of Ni‐rich cathode materials. In this study, interphase engineering improves the interphase stability of LiNi0.83 Co0.11 Mn0.06 O2 in lithium‐ion batteries. A robust cathode‐electrolyte interphase is constructed by a nucleophilic reaction in the commercial electrolyte and the cathode achieves long‐term cycling stability in a Li||NCM83 cell.